EFEKTIFITAS KINESIO TAPING UNTUK PENURUNAN NYERI PUNGGUNG BAWAH (STUDI KUASI EKSPERIMENTAL PADA PASIEN NYERI PUNGGUNG BAWAH) - Abdurahman Berbudi B L; Achwan Achwan; Nina Mustika Sari (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background: Low back pain results in decreased activity in daily activities. The tapping method is an active therapy that uses tension in the muscles to maintain a position to reduce pain and disability and increase spinal mobility. Taping is a rehabilitative technique used to facilitate the body's natural healing process while providing support and stabilization to muscles and joints without limiting the range of motion of the joints. Objective: To determine the effect of tapping and taping on reducing the degree of pain in low back pain. Methods: This research is a pre-experimental type with a one-group pretest-posttest approach. The data used are age and degree of pain. Results: From the study results, the average degree of pain before the intervention was 5.10, and the value after the taping intervention was 4.03. Wilcoxon test results showed the value of P = 0.008 (p < 0.05). And for the provision of tapping, the average degree of pain before was 4.93 and after 2.67 with p = 0.0001 (p <0.05). Conclusion: It is concluded that taping decreases the degree of pain in low back pain. Suggestion: The results of this study can be used as a reference for reducing the degree of pain in low back pain.